Faktor-Faktor yang Mempengaruhi Perilaku Individu dalam Organisasi - Sigit Riyadi; Tantri Widiastuti (STIE Widya Manggala, 2013)
This study aimed to analyze the influence of Variabels of individual, psychological, and organization on the behavior of individuals in Mataram Sakti of Branch Mijen. The population in this study was 40 people that is the whole staff and all population was sampled. The analytical tool used in this study was multiple linearregression. The results showed that the individual, psychological, and organizational significantly influence the behavior of individuals in Mataram Sakti of Branch Mijen.